2003
DOI: 10.1086/375207
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Occupation in the Kuiper Belt: Case Examples of the 52 and Trojan Resonances

Abstract: As part of our ongoing Deep Ecliptic Survey (DES) of the Kuiper belt, we report on the occupation of the 1:1 (Trojan), 4:3, 3:2, 7:4, 2:1, and 5:2 Neptunian mean-motion resonances (MMRs). The previously unrecognized occupation of the 1:1 and 5:2 MMRs is not easily understood within the standard model of resonance sweeping by a migratory Neptune over an initially dynamically cold belt. Among all resonant Kuiper belt objects (KBOs), the three observed members of the 5:2 MMR discovered by DES possess the largest … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
136
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(140 citation statements)
references
References 37 publications
3
136
1
Order By: Relevance
“…3 during 1 Gyr, except Trojan 2001QR322, which escapes from the Lagrangian L 4 point after about 112 Myr. This last observation was somehow unexpected, since Chiang et al (2003) concluded that this same Neptune Trojan was stable over 1 Gyr. This difference of behaviors is a consequence of a modification in the initial conditions (Table A.3), obtained with new observational data.…”
Section: Stability Of the Neptune Trojansmentioning
confidence: 91%
“…3 during 1 Gyr, except Trojan 2001QR322, which escapes from the Lagrangian L 4 point after about 112 Myr. This last observation was somehow unexpected, since Chiang et al (2003) concluded that this same Neptune Trojan was stable over 1 Gyr. This difference of behaviors is a consequence of a modification in the initial conditions (Table A.3), obtained with new observational data.…”
Section: Stability Of the Neptune Trojansmentioning
confidence: 91%
“…The Kuiper belt population is in turn subdivided in two sub-populations: the resonant population (star symbols in Figure 1) and the classical belt (dots). The former is made of the objects located in some major mean motion resonance with Neptune (essentially the 3:4, 2:3 and 1:2 resonances, but also the 2:5 -see Chiang et al, 2003), while the classical belt objects are not in any noticeable resonant configuration. It is well known that mean motion resonances offer a protection mechanism against close encounters with the resonant planet (Cohen and Hubbard, 1965).…”
Section: The Trans-neptunian Populationsmentioning
confidence: 99%
“…This resonance occupancyreinforces the finding that there are many TNOs in high-order, distant > a 50 resonances (Chiang et al 2003;Lykawka & Mukai 2007a;Gladman et al 2008;2012;Alexandersen et al 2014;Pike et al 2015;Kaib & Sheppard 2016;Sheppard et al 2016). Objects in large-a resonances are inefficiently discovered due to ther 4 dependence for reflected flux, the overall steep TNO luminosity function, and because the large eccentricities of such orbits placemost of the population at large distances at any given timeand thus below the flux limit of wide-field surveys.…”
Section: Orbitmentioning
confidence: 85%